Listen, beautiful Marcia - Quintanilha, Marcello, 1971- (Fantagraphics Books Inc., 2023)
"Listen, Beautiful Márcia is a gripping story about a family pushed to the brink. Márcia is a nurse in a hospital near Rio and lives in a favela with her boyfriend, Aluisio, and her daughter, Jaqueline, whom she had very young with another man. Jaqueline, a troubled young adult, makes life difficult for her mother and Aluisio and rebelliously hangs out with members of a neighborhood gang, leading to violent altercations between mother and daughter. The situation degenerates even more when Jaqueline is arrested. Márcia and Aluisio, distraught, realize that Jaqueline is in deeper trouble than they ever thought. Listen, Beautiful Márcia is a fast-paced, flamboyantly colorful new graphic novel by one of the most important Brazilian graphic novelists working today. Marcello Quintanilha's first English-language graphic novel is a tour de force -- a tightly wound drama filled with masterful suspense and a deep love for family and character."--Publisher.